Spatial distribution of benthic invertebrates in Lake Winnebago, WI - Heling, Courtney L. (My University, 2017)
Numerous studies have examined the distribution of benthic invertebrates in lakes through space and time. However, most studies typically focus on single habitats or individual taxa rather than sampling comprehensively in multiple habitats in a single system. The focus of this study was to quantify the spatial distribution of the macroinvertebrate taxa present in three major lake zones (profundal, offshore reef, and littoral) in Lake Winnebago, Wisconsin, with a particular emphasis on chironomid distribution, and to determine what factors drove patterns in variation. The profundal zone was sampled for two consecutive years in August to determine if changes in spatial variation occurred from one year to the next. Using a variety of sampling methods, invertebrates were collected from all three zones in 2013 and the profundal zone in 2014. Additionally, numerous physical and biological variables were measured at each sampling site. Benthic invertebrate densities ranged from 228 to 66,761 individuals per m2 and varied among lake zones and substrates. Zebra mussels (Dreissena polymorpha) were numerically dominant in both the offshore reef and littoral zones, while chironomids and oligochaetes comprised approximately 75% of profundal invertebrates sampled. Principal components analysis (PCA) showed that chironomid community structure differed highly among the three major lake zones. The littoral and offshore reef zones had the highest chironomid taxa richness, while the profundal zone, where Procladius spp. and Chironomus spp. were dominant, had lower richness. Chironomid density and community structure exhibited spatial variation within the profundal zone. The abundance of chironomids was correlated with several habitat variables, including organic matter content of the sediments. As aquatic systems undergo rapid modification due to the introduction of invasive species, eutrophication, and climate change it has become increasingly important to conduct comprehensive studies, such as this one, to better assess the manner in which these systems respond and adapt to change.
A Thesis Submitted In Partial Fulfillment of the Requirements For the Degree of Master of Science - Biology
Keywords: Lake Winnebago, Wisconsin; Stream ecology; Lake animals; Freshwater invertebrates; Zebra mussel